Tonsillotomy by a Fractional Carbon Dioxide Laser: A New Technique in the Treatment of Chronic Tonsillitis: Fractional Carbon Dioxide Laser Controls Chronic Tonsillitis - Costa, Heloisa Juliana Zabeu Rossi; Di Francesco, Renata Cantisani; Giancoli, Suzana Maria; De Miranda, Fernando Mathias Pereira; Bento, Ricardo Ferreira (Journal of Lasers in Medical Sciences, 2022)
Introduction: chronic tonsillitis has a global prevalence ranging from 5-12%. Its clinical manifestations, like recurrent acute tonsillitis, tonsils hypertrophy, caseum and halitosis, can lead adult patients to be submitted to palatine tonsillectomy, surgery that has morbidity and the potential risk of complications, including severe bleeding. This article proposes a new therapy for chronic tonsillitis in adult patients using a fractional carbon dioxide (CO2) laser, a fast, minimally invasive procedure capable of removing the need for the traditional tonsillectomy in many patients. Objective: to verify the efficacy of tonsillotomy by fractional ablation using the CO2 laser by comparing number of bacterial infections, tonsils hypertrophy, halitosis and caseum; to analyze the benefits, risks and complications of the technique. Methods: 20 patients were subjected to one session of tonsillotomy by fractional ablation and were followed up on for a year. The control group was formed by the same patients in the pre-procedure period (one year) without treatment. Results: no complications occurred, the procedure was fast (30 seconds), safe and tolerated well without general anesthesia. After one year, there was a total remission of recurrent acute tonsillitis in 95% of the patients, and after six months there was a statistically significant improvement of halitosis and caseum, and tonsils size reduction (p<0,05). The level of satisfaction average was 10 after three months and 8 after one year. Conclusion: tonsillotomy by fractional ablation using the CO2 laser is a safe, efficient procedure for chronic tonsillitis in adults, which can be incorporated into the daily clinical practice.